Emerging crosstalk between long non-coding RNAs and Nrf2 signaling. (10th October 2020) - Bhattacharjee, Shamee; Li, Jia; Dashwood, Roderick H.
Abstract: Diverse stimuli trigger Nrf2 signaling, which in turn transcriptionally regulates an array of downstream targets, providing for multiple layers of control. While Nrf2 activity largely is governed by posttranslational modification of critical thiol residues in the protein partner and redox sensor Keap1, fine-tuning is provided by additional mechanisms – including epigenetic regulation. Herein, we review the emerging significance of long non-coding RNAs (lncRNA) as downstream targets and upstream regulators of the Nrf2 signaling pathway. Among the 16000 lncRNAs in GENCODE, some have been validated as transcriptionally regulated by Nrf2 (e.g., LUCAT1, NMRAL2P, ODRUL, ROR and TUG1 ), and others have been identified as upstream regulators of Nrf2 expression (e.g., HOTAIR, MALAT1, MEG1, NRAL and UCA1 ). Bioinformatic analyses of annotated human lncRNAs identified putative Nrf2 binding sites in the promoter regions of 13, 285 lncRNAs. Further investigation is warranted to validate the many novel lncRNAs as bona fide Nrf2-regulated targets, and their roles in Nrf2 signaling. Nrf2 is considered a promising therapeutic candidate for cancer and other chronic diseases; thus, targeting the associated lncRNAs might provide for a more refined fine-tuning of the system, depending on cellular and pathophysiological context. Highlights: LncRNAs are emerging as critical players in the Nrf2 signaling network. A few lncRNAs are downstream transcriptional targets of Nrf2. Some others also act as upstream regulators of Nrf2 activity. Bioinformatics approaches identified 13, 285 ARE sequences in human lncRNA promoters. Targeting these lncRNAs might enable context-specific regulation of Nrf2 signaling in oncology.